Seasonal variations in the occurrence of Golovinomyces orontii and Podosphaera xanthii, causal agents of cucurbit powdery mildew in Northern Italy. (18th June 2015) - Pirondi, A.; Pérez‐García, A.; Battistini, G.; Muzzi, E.; Brunelli, A.; Collina, M.
Abstract Powdery mildew, caused by Golovinomyces orontii and Podosphaera xanthii, is a widespread disease that causes important losses in cucurbit production. To determine the aetiology and the epidemiology of cucurbit powdery mildew disease in the North of Italy, observations on the occurrence of the main disease‐causing fungal species were conducted during the 2010, 2011 and 2012 growing seasons. Samples of infected leaves of zucchini, melon and pumpkin plants, either from field or greenhouse crops, were collected every 15–18 days from May to September/October. To identify the fungal species, both morphological observations based on the asexual stage and molecular identifications by a Multiplex‐PCR reaction with species‐specific primers were performed. Climatic parameters of temperature and relative humidity were also monitored. Pearson's correlation coefficient and Principal Component Analysis showed a negative significant correlation between the two species, and a peculiar epidemiological behaviour was also observed: the earlier infections were caused by G. orontii, which was the predominant species till the end of June–middle of July. At this time, this species progressively decreased in frequency and was replaced by P. xanthii that became the main species infecting cucurbits till the end of the growing season. As the two species have different ecological requirements, these seasonal variations in the cucurbit powdery mildew species composition could possibly be explained by the influence of temperature and relative humidity on the pathogen epidemiology during the growing season but also by the different overwintering strategies adopted by the two species.